MS-based Lipidomic Profiling of Oxylipins Supports Mild Inflammation in Dysmetabolic Iron Overload Syndrome Affected Patients (P08-046-19). (24th October 2019) - Dalle, Céline; Lahaye, Clément; Bosviel, Rémy; Ruivard, Marc; Gladine, Cecile; Mazur, André
Abstract: Objectives: Insulin resistance-associated hepatic iron overload, referred as dysmetabolic iron overload syndrome (DIOS) associates a mild increase of both liver and body iron stores and various components of the metabolic syndrome (MetS). DIOS occurrence is frequent and concerns up to 20% of patients with MetS. The causes and clinical relevance of DIOS are still misunderstood. Oxylipins refer to a large family of signaling lipids notably involved in the regulation of inflammation. We hypothesized that iron overload in DIOS could be associated with an altered oxylipin profile reflecting the dysregulation of inflammatory and oxidative stress status. Methods: This case-control study involved 20 subjects with DIOS (DIOS), 20 subjects with metabolic syndrome without iron overload (MetS) and 20 healthy control subjects (Healthy). Oxylipin profiling was performed in plasma of each participant using mass spectrometry (MS)-based lipidomic profiling. Results: Univariate analysis identified eleven oxylipins significantly higher in the DIOS group in comparison with MetS and healthy subjects. These include (i) prostaglandin D2 which is produced from arachidonic acid (AA) via the cylcooxygenase action, (ii) 8-hydroxy fatty acids including 5-HETE and 15-HETE, well known mediators of inflammation derived from AA via the lipooxygenase pathway, and (iii) two oxylipins of the cytochrome P450 pathways, namely 14, 15-EET and 5, 6-DiHETE. Of notes, PGD2 as well as 5- and 15-HETE are mediators of inflammation. Multivariate analysis including hierarchical cluster analysis and PCA did not discriminate subjects from the different groups. Conclusions: Iron overload in DIOS was associated with moderate alterations of the oxylipin profile suggesting a mild inflammation, but larger sample size would be necessary to confirm results from this pilot study. Funding Sources: This study was funded by the University Hospital of Clermont-Ferrand and by the French Society of Internal Medicine.